1996
DOI: 10.1111/j.1349-7006.1996.tb02128.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cytocidal Activity of OK‐432‐activated Mononuclear Cells against Human Glioma Cells is Partly Mediated through the Fas Ligand/Fas System

Abstract: We have been applying an adoptive immunotherapy protocol to patients with malignant brain tumors using OK‐432‐activated peripheral blood mononuclear cells (OK‐MCs). In order to elucidate the mechanism of OK‐MCs' cytotoxicity, we examined the expression of Fas ligand mRNA in OK‐MCs and the cytocidal activity of these cells against a human glioma cell line, T98G which expresses a high level of Fas. The expression of Fas ligand mRNA was low in non‐treated peripheral blood mononuclear cells and was elevated by tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…Recently, it was reported that the expression of perforin in cytotoxic CD8 + T cell is required to moderate allergic airway inflammation [ 29 ]. In line with this, the induction of perforin and enhanced expression of Fas-ligand are shown in OK-432-activated monocytes [ 30 , 31 ], suggesting that an apoptosis-related mechanism might also be involved in controlling pulmonary eosinophilia by OK-432.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, it was reported that the expression of perforin in cytotoxic CD8 + T cell is required to moderate allergic airway inflammation [ 29 ]. In line with this, the induction of perforin and enhanced expression of Fas-ligand are shown in OK-432-activated monocytes [ 30 , 31 ], suggesting that an apoptosis-related mechanism might also be involved in controlling pulmonary eosinophilia by OK-432.…”
Section: Discussionmentioning
confidence: 77%
“…OK-432 is an immunomodulatory agent prepared from an avirulent human strain of Streptococcus pyogenes. It has been shown to induce various cytokines, especially Th1 cytokines (Saito et al, 1982;Yamamoto et al, 1986;Yang et al, 1992) and to upregulate both perforin (Kataoka et al, 1991) and Fas ligand expression (Toda et al, 1996;Sato et al, 1997) of immune cells. In accordance with these findings, OK-432 is also known to enhance or activate the cytotoxic activity of various effector cells (Ishii et al, 1976;Uchida and Micksha, 1983), which may be responsible for its therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with these findings, OK-432 is also known to enhance or activate the cytotoxic activity of various effector cells (Ishii et al, 1976;Uchida and Micksha, 1983), which may be responsible for its therapeutic effect. The augmentation of perforin (Kataoka et al, 1991), induction of IL-2 and IFN-γ, and the upregulation of Fas ligand (Toda et al, 1996;Sato et al, 1997) by OK-432 may play a major role in promoting anti-tumour necrotic and apoptotic effects of immune cells like NK cells, LAK cells, CTL (Kagii et al, 1994;Lowin et al, 1994;Lin et al, 1995;Frost et al, 1997), and TILs. These such biological activity of OK-432 are thought to occur at the tumour site in the case of intratumoral injection of OK-432.…”
Section: Discussionmentioning
confidence: 99%
“…However, this principle is difficult in practice because the most effective anticancer drugs are generally used during primary treatment. A combination of UFT and OK-432 or another combination of anticancer drugs and an immunopotentiator is recommended in distant metastases because drugs possess not only potent cancer cell growth-inhibitory activity but also induce tumor cell apoptosis [45, 46]and cytotoxic lymphocytes [47, 48]required for successful treatment.…”
Section: Discussionmentioning
confidence: 99%